Attributable mortality of ICU-acquired bloodstream infections: Impact of the source, causative micro-organism, resistance profile and antimicrobial therapy. Issue 2 (February 2017) - Adrie, Christophe; Garrouste-Orgeas, Maité; Ibn Essaied, Wafa; Schwebel, Carole; Darmon, Michael; Mourvillier, Bruno; Ruckly, Stéphane; Dumenil, Anne-Sylvie; Kallel, Hatem; Argaud, Laurent; Marcotte, Guillaume; Barbier, Francois; et al.
Summary: Objectives: ICU-acquired bloodstream infection (ICUBSI) in Intensive Care unit (ICU) is still associated with a high mortality rate. The increase of antimicrobial drug resistance makes its treatment increasingly challenging. Methods: We analyzed 571 ICU–BSI occurring amongst 10, 734 patients who were prospectively included in the Outcomerea Database and who stayed at least 4 days in ICU. The hazard ratio of death associated with ICU–BSI was estimated using a multivariate Cox model adjusted on case mix, patient severity and daily SOFA. Results: ICU–BSI was associated with increased mortality (HR, 1.40; 95% CI, 1.16–1.69; p  = 0.0004). The relative increase in the risk of death was 130% (HR, 2.3; 95% CI, 1.8–3.0) when initial antimicrobial agents within a day of ICU–BSI onset were not adequate, versus only 20% (HR, 1.2; 95% CI, 0.9–1.5) when an adequate therapy was started within a day. The adjusted hazard ratio of death was significant overall, and even higher when the ICU–BSI source was pneumonia or unknown origin. When treated with appropriate antimicrobial agents, the death risk increase was similar for ICU–BSI due to multidrug resistant pathogens or susceptible ones. Interestingly, combination therapy with a fluoroquinolone was associated with more favorable outcome than monotherapy, whereas combination with aminoglycoside was associated with similar mortality than monotherapy. Conclusions: ICU–BSI was associated with a 40% increase in the risk of 30-day mortality, particularly if the early antimicrobial therapy was not adequate. Adequacy of antimicrobial therapy, but not pathogen resistance pattern, impacted attributable mortality. Highlights: Bloodstream Infection acquired in ICU was associated with an increase in the risk mortality. Early adequate antimicrobial therapy was associated with a better outcome. This was true whatever the susceptibility of the causative bacteria. Fluoroquinolone use, but not aminoglycoside use, was associated with an improved outcome.